How social media Reshapes Indigenous Political Power: A Critical Study of Digital Counter publics in Nepal (Voice of Teacher, 2025)
This paper will analyze the ways in which social media is transforming Indigenous political participation in Nepal by facilitating new ways of expressing political voice, identity and political action among Indigenous nationalities (Janajati). Nepal has a history of the political, cultural and linguistic marginalization of the indigenous communities, which have led to the underrepresentation of indigenous populations in mainstream politics and media. As digital communication technologies continue to multiply at an alarming rate, the social media platforms have become alternative venues where Indigenous communities can conduct political discussions and activism. Based on the theoretical lenses of Communication for Empowerment, public sphere theory and counter public theory, and networked activism, this paper will conceptualize Indigenous-oriented social media spaces as digital counter publics. The study has a qualitative descriptive research methodology based on critical digital ethnography. Data were created by a combination of sustained digital observation, semi-structured interviews of 50 Indigenous participants, four focus group discussions and qualitative content analysis of about 360-420 publicly available social media posts, videos, comment threads and live stream transcripts on Facebook, Tik Tok, YouTube, and X.The results indicate that social media increases Indigenous political voice and visibility, facilitates building of digital counter publics, allows culture and linguistic expression to be turned into political agent, as well as quick mobilization in politics. Simultaneously, Indigenous online involvement is still limited by digital injustices, the lack of platform support of Indigenous languages, algorithmic bias, web-based harassment, and surveillance-related issues. These influence unequal participation and inhibit the transformative nature of social media. The paper contends that social media does not dismantle structural inequalities but reinvents the landscape of Indigenous politics by changing the manner in which voices are generated, distributed and resisted in digital politics. The study adds to digital politics and Indigenous media research in the Global South and shows the necessity to establish all-inclusive digital governance, protect digital rights, and support Indigenous-led digital action.